Christ’s crucifixion as a medico-historical event - Retief, Francois P.; Cilliers, Louise (Acta Theologica, 2005)
The crucifixion of Christ as a medico-historical event is reviewed. He was probably crucified on a short Tau-cross, and died within 6 hours (probably even within 3 hours). This is not an exceptionally short period of time, and there is no reason to postulate unusual causes for his death. He probably died from the classical progressive asphyxia syndrome and hypovolaemic shock typical of the crucifixion process, finally ending in cardiac arrest as result of a vaso-vagal reflex. The latter could have been elicited by intense pain due to various causes, although hypoxaemia per se or various other less common conditions could also have pertained. The wound in Christ’s side from the spear which probably pierced his heart, was certainly inflicted after his death. The appearance of blood and water as an expected post mortem phenomenon is discussed. There is no reason to consider this as proof of a functioning blood circulation indicating apparent rather than true death. Although the two robbers who were crucified with Christ were apparently still alive when He died, they were dispatched shortly afterwards by crurifragium.